1992
DOI: 10.1161/01.cir.86.1.232
|View full text |Cite
|
Sign up to set email alerts
|

Lumen diameter of normal human coronary arteries. Influence of age, sex, anatomic variation, and left ventricular hypertrophy or dilation.

Abstract: BACKGROUND Precise knowledge of the expected "normal" lumen diameter at a given coronary anatomic location is a first step toward developing a quantitative estimate of coronary disease severity that could be more useful than the traditional "percent stenosis." METHODS AND RESULTS Eighty-three arteriograms were carefully selected from among 9,160 consecutive studies for their smooth lumen borders indicating freedom from atherosclerotic disease. Of these,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

32
372
3
4

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 674 publications
(411 citation statements)
references
References 52 publications
32
372
3
4
Order By: Relevance
“…Curiously, Lip et al [23] found in indoasian people a narrower caliber of 2.98 mm. Equally with our results, Dodge et al [21] and Kaimkhani et al [24], found a correlation between coronary dominance and caliber, being higher in hearts with right dominance. We found larger calibers in LCA than RCA.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Curiously, Lip et al [23] found in indoasian people a narrower caliber of 2.98 mm. Equally with our results, Dodge et al [21] and Kaimkhani et al [24], found a correlation between coronary dominance and caliber, being higher in hearts with right dominance. We found larger calibers in LCA than RCA.…”
Section: Discussionsupporting
confidence: 92%
“…We found larger calibers in LCA than RCA. These findings are consistent with angiographic and post-morten measurements [19][20][21][22][23][24] .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings may thus explain the high variability in the prevalence of hot spots in different vascular districts, as plaque growing in smaller-diameter vessels, such as the carotid and coronary arteries, are more likely to be identified even at an initial stage (23)(24)(25). Conversely, plaque developing in larger vessels can be relatively asymptomatic; such segments may thus house clinically undetected initial-, intermediate-, and end-stage cold plaque.…”
Section: Discussionmentioning
confidence: 80%
“…The conclusion of their study was that a margin of 2 mm in the A-P and L-R plane and of 4 mm in the inferior-superior plane should be added on the contour delineated by the physician [23]. In a study by Dodge et al, using arteriograms, the diameter of LAD is estimated to 3,7±0,4 mm in the proximal and to 1,9±0,4 mm in the distal parts [24]. In terms of cardiac and respiratory motion, a diameter of 6 mm when delineating the LAD should be considered as sufficient based on the results of the present study and the study by White et al [23].…”
Section: Discussionmentioning
confidence: 97%